2014
DOI: 10.1177/2150135113515487
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcome of Primary Arterial Switch Operation Beyond Six Weeks of Life in Children With Transposition of Great Arteries and Intact Ventricular Septum

Abstract: Primary ASO can be safely performed in children with regressed ventricle, irrespective of age with encouraging results. The midterm results of these children are comparable in terms of survival and freedom from complications associated with preserved ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Primary ASO may be used in patients older than 2 months of age with only slight increase in early morbidity and mortality, with 5.7% requiring postoperative mechanical assistance in one study [70]. Other studies show comparable outcomes of the late ASO in children up to 8 years of age, with only a mild increase in morbidity and resource consumption [7174]. Those undergoing the two-stage ASO fared the worst.…”
Section: The “Late” Asomentioning
confidence: 99%
“…Primary ASO may be used in patients older than 2 months of age with only slight increase in early morbidity and mortality, with 5.7% requiring postoperative mechanical assistance in one study [70]. Other studies show comparable outcomes of the late ASO in children up to 8 years of age, with only a mild increase in morbidity and resource consumption [7174]. Those undergoing the two-stage ASO fared the worst.…”
Section: The “Late” Asomentioning
confidence: 99%
“…Although an increased need for ECMO support has been reported in late ASO patients, this was not accompanied by an increase in mortality. Bisoi et al [5] reported 20% of ECMO support and 3.7% mortality in a series of 109 late ASO patients. However, late mortality was reported separately from primary disease.…”
Section: Discussionmentioning
confidence: 98%
“…The arterial switch procedure is a question of debate in patients with TGA/IVS after three weeks of age due to the LV structure and function loss. Recently, because of the potential medium-to long-term complications of these operative procedures, there has been an increase in reports of successfully performed arterial switch procedures after the 3 rd week of life with the aid of improvements in advanced life support systems [4,5] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations